A kind of anti-rutting epoxy resin concrete and preparation method thereof
By using epoxy resin fibers and modified asphalt in concrete, combined with a conjugated system of rice husk carbon-loaded silica nanospheres and 2,4-dihydroxybenzophenone, the concrete is compressive and UV resistance. The problem of aging achieves higher compressive strength and better mechanical properties.
Patent Information
- Application Number
- CN202311818528.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-12-27
AI Technical Summary
Existing concrete materials have low compressive strength and are susceptible to cracks caused by ultraviolet aging. They are severely damaged in traffic-intensive areas and ramps, which cannot meet market demand.
Using the combination of epoxy resin fibers and modified asphalt, the silica nanospheres supported by rice husk carbon and 2-aminoethylamine methyltriethoxysilane are modified to form a covalent bond link to increase interfacial tension; 2,4-dihydroxybenzophenone is introduced into the asphalt and reacts with amino polyethylene glycol acrylate to form a conjugated system to shield the ultraviolet rays and enhance the compressive and UV resistance of the concrete.
It significantly improves the compressive strength and UV aging resistance of concrete, forms a more stable structure, prevents the spherical effect of fibers, and enhances the mechanical properties of concrete.
Smart Images

Figure BDA0004633311370000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, in particular to an anti-rutting epoxy resin concrete and a preparation method thereof. Background Art
[0002] Due to the continuous development of society, the government has invested a lot of money to strengthen the country's infrastructure. Many cities or rural areas are building roads, and the demand for concrete floors is gradually increasing. However, on the market, general concrete floors are currently made of cement and sand, and such floors have low compressive strength and do not meet market demand. Secondly, coupled with ultraviolet aging caused by sunlight, its ductility decreases, which can easily cause cracks in the road surface, especially at intersections, bus ports, uphill and downhill locations; therefore, it is particularly important to invent a rutting-resistant concrete. Summary of the invention
[0003] The object of the present invention is to provide an anti-rutting epoxy resin concrete and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: an anti-rutting epoxy resin concrete, which is made of epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone chips, fly ash, triterpene saponin air entraining agent, melamine water reducer and deionized water.
[0005] Furthermore, the epoxy resin fiber is prepared by melt spinning modified rice husk charcoal composite silica nanospheres, hexahydrophthalic anhydride and epoxy resin E51.
[0006] Furthermore, the modified rice husk charcoal composite silica nanospheres are prepared from rice husk charcoal composite silica nanospheres modified by 2-aminoethylaminomethyltriethoxysilane.
[0007] Furthermore, the modified asphalt is prepared by modifying asphalt with modified 2,4-dihydroxybenzophenone and calcium chloride.
[0008] Furthermore, the modified 2,4-dihydroxybenzophenone is prepared from 2,4-dihydroxybenzophenone and amino polyethylene glycol acrylate.
[0009] Furthermore, a method for preparing anti-rutting epoxy resin concrete comprises the following preparation steps:
[0010] (1) Rice husk powder, sodium hydroxide and deionized water are mixed in a mass ratio of 0.8:0.8:3.6-1.2:1.2:4.4, stirred evenly, heated to 70-90°C, stirred at 100-200 rpm for 4-6 hours, cooled to room temperature, filtered, solids are washed with deionized water for 4-8 times, vacuum dried at 50-70°C for 10-15 hours, ground until passing through a 400-800 mesh sieve, methanol 2-4 times the mass of rice husk powder, ethyl orthosilicate 3-6 times the mass of rice husk powder, and 0.8 mol / L dilute hydrochloric acid 1-2 times the mass of rice husk powder are added, stirred at 250-300 rpm for 30-60 hours, filtered, solids are washed with deionized water 2-5 times, dried at -45--50°C for 20-26 hours, and calcined at 700-800°C for 4-8 hours to obtain rice husk carbon composite silica nanospheres;
[0011] (2) Mix the rice husk charcoal composite silica nanospheres with 2-aminoethylaminomethyltriethoxysilane in a mass ratio of 1:1, place in toluene with a mass of 25 to 30 times that of 2-aminoethylaminomethyltriethoxysilane, heat to 95 to 105° C. under nitrogen protection, stir at 70 to 100 rpm for 10 to 14 hours, filter, take the solid, wash it twice with dichloromethane and ethanol respectively, and vacuum dry it at 80 to 110° C. for 3 to 6 hours to obtain modified rice husk charcoal composite silica nanospheres;
[0012] (3) Mixing epoxy resin E51 and hexahydrophthalic anhydride, stirring at 70-100 rpm for 10-30 min, ultrasonicating at 20-40 kHz for 60-100 min, adding n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres, stirring at 100-200 rpm for 3-6 h, performing melt spinning, and curing at 90-120° C. for 3-6 h to obtain epoxy resin fibers;
[0013] (4) 2,4-dihydroxybenzophenone and anhydrous ethanol are mixed in a mass ratio of 20:95 to 24:110 and placed in an ice water bath at 0 to 4°C, 8 wt% sodium hydroxide aqueous solution in an amount of 5.4 to 7.2 times the mass of 2,4-dihydroxybenzophenone is added dropwise at 0.3 to 0.7 mL / s, the mixture is reacted for 30 to 60 min, dimethyl sulfate in an amount of 1.5 to 2 times the mass of 2,4-dihydroxybenzophenone is added, the mixture is stirred at 70 to 100 rpm for 10 to 14 h, filtered, the solid is taken, and washed 2 to 4 times with 8 wt% sodium hydroxide aqueous solution and anhydrous ethanol, respectively, to obtain intermediate A;
[0014] (5) Mixing intermediate A and N,N-dimethylformamide in a mass ratio of 9:4 to 10:6, stirring at 70 to 100 rpm for 20 to 30 min to obtain a mixed solution; placing N,N-dimethylformamide in a 0 to 4°C ice water bath, adding a mixed solution of 0.9 to 1.1 times the mass of N,N-dimethylformamide in phosphorus oxychloride and 2.8 to 3.4 times the mass of N,N-dimethylformamide at a rate of 0.1 to 0.3 mL / s, heating to 70 to 80°C, reacting for 3 to 6 hours, cooling to room temperature, adding 20 to 25 times the mass of N,N-dimethylformamide in deionized water at 0 to 4°C and 1 to 1.5 times the mass of N,N-dimethylformamide in a 10 wt% sodium carbonate aqueous solution, filtering, taking the solid, washing with deionized water 1 to 3 times, adding anhydrous ethanol 4 to 7 times the mass of N,N-dimethylformamide, standing for 1 to 2 hours, filtering, taking the solid, and obtaining intermediate B;
[0015] (6) Under nitrogen protection, aluminum chloride, intermediate B, and dichloromethane are mixed in a mass ratio of 1.5:1:13 to 3:1.7:17, stirred at 70 to 100 rpm for 3 to 6 hours, 6 to 8 times the mass of dichloromethane, 0 to 4°C deionized water is added, and the solution is adjusted to pH 5 with hydrochloric acid, filtered, the solid is taken, washed with saturated sodium chloride solution 1 to 3 times, 5 wt% sodium hydroxide aqueous solution is added to the solution pH of 8 to 10, and then dilute hydrochloric acid is added to the solution pH of 5 to 6, and the solution is allowed to stand for 30 to 60 minutes, filtered, the solid is taken, washed with deionized water 1 to 3 times, and dried at 50 to 70°C for 3 to 6 hours to obtain modified 2,4-dihydroxybenzophenone;
[0016] (7) aminopolyethylene glycol acrylate, distilled water, and anhydrous ethanol are mixed in a mass ratio of 0.8:0.8:16 to 1.2:1.2:24, modified 2,4-dihydroxybenzophenone is added in an amount of 4 to 8 times the mass of aminopolyethylene glycol acrylate, and stirred at 70 to 100 rpm for 4 to 6 hours, a 0.5 mol / L calcium chloride aqueous solution is added in an amount of 4 to 6 times the mass of aminopolyethylene glycol acrylate, and the mixture is soaked at 33 to 40° C. for 3 days, and No. 90 base asphalt is added in an amount of 36 to 44 times the mass of aminopolyethylene glycol acrylate and hexadecyltrimethylammonium chloride is added in an amount of 5 to 10 times the mass of aminopolyethylene glycol acrylate, the temperature is raised to 130 to 160° C., and stirred at 3000 to 5000 rpm for 20 to 40 minutes to obtain modified asphalt;
[0017] (8) Mix the epoxy resin fiber and modified asphalt, heat to 105-130°C, stir at 150-250 rpm for 4-8 hours, let stand for 1-2 hours, add silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water, stir at 20-30 Hz and 100-200 rpm for 30-50 minutes to obtain rutting-resistant epoxy resin concrete.
[0018] Furthermore, the vacuum degree in step (1) and step (2) is both 0.2 to 1 kPa.
[0019] Furthermore, the melt spinning conditions in step (3) are: temperature of 190-230° C., melt viscosity of 200-250 Pa×s, and tensile strength of 8.8-11.5 MPa.
[0020] Furthermore, in step (3), the mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres is 50:46.5:2.3:5 to 70:68.2:4.2:8.
[0021] Furthermore, in step (8), the mass ratio of the epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer and deionized water is 1:120:48:160:134:17:1:0.5:30-2:160:56:180:154:21:1.2:0.7:40.
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0023] The concrete of the invention is prepared by mixing epoxy resin fiber and modified asphalt to achieve the effects of compression resistance and UV resistance.
[0024] Firstly, the present invention uses rice husk charcoal to load on mesoporous silica to improve the rigidity and hardness of silica, and indirectly improve the compressive strength of concrete; then, 2-aminoethylaminomethyltriethoxysilane is used to modify it, and after melt spinning with epoxy resin and hexahydrophthalic anhydride, heat treatment is performed to open the amino group of 2-aminoethylaminomethyltriethoxysilane and the epoxy group to form a covalent bond link, thereby generating a strong interfacial tension; when subjected to external force, the interface between the rigid rice husk charcoal composite silica nanosphere and the resin matrix is destroyed to absorb a large amount of energy, and the generated holes make the concrete ... The local strain capacity of the epoxy resin cross-linked network is improved, the stress transfer is more uniform, and the expansion of silver streaks in the resin matrix can be effectively inhibited, thereby strengthening the epoxy resin and indirectly improving the compressive strength of the concrete. At the same time, the hydroxyl groups produced by the ring opening react with the anhydride groups of hexahydrophthalic anhydride, thereby increasing the three-dimensional cross-linking degree inside the epoxy resin fiber and forming a more stable structural morphology, which is interspersed in the concrete to play a supporting structure. With the assistance of nanospheres, the fiber balling effect is effectively prevented, which is equivalent to a secondary reinforcement effect and greatly improves the compressive strength of the concrete.
[0025] Secondly, an aldehyde group is introduced into the benzene ring of 2,4-dihydroxybenzophenone, and then an addition dehydration reaction is carried out with the amino group in aminopolyethylene glycol acrylate to introduce carbon-nitrogen double bonds, carbon-carbon double bonds and benzene rings to form a conjugated system in the asphalt, which can shield and absorb ultraviolet rays, so that the matrix can achieve a strong anti-ultraviolet effect. Then, the hydroxyl group is combined with calcium ions to stimulate the adhesion between the asphalt and the rigid particles in the epoxy resin fiber, so that the asphalt particles serve as the connection point of the epoxy resin fiber "bridge", thereby forming a dense and locked structure inside the concrete, jointly bearing external forces, and significantly improving the mechanical properties of the concrete and enhancing the compressive resistance. At the same time, the compatibility between aminopolyethylene glycol acrylate and asphalt is also enhanced, thereby enhancing the anti-ultraviolet effect of the concrete. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the anti-rutting epoxy resin concrete prepared in the following examples are as follows:
[0028] Rutting resistance: The concrete of the embodiment and the comparative example was made into specimens with a thickness of 80 mm, and the dynamic stability of the specimens was tested with reference to JTG E20.
[0029] Compression resistance: The concrete of the embodiment and the comparative example was made into specimens with a size of 100 mm×100 mm×100 mm, and the compressive strength test of the specimens at different ages was carried out with reference to GB / T50081.
[0030] Anti-ultraviolet: Take the embodiment and comparative example of the same size and conduct carbonization test according to GB / T50082.
[0031] Example 1
[0032] (1) Rice husk powder, sodium hydroxide and deionized water were mixed in a mass ratio of 0.8:0.8:3.6, stirred evenly, heated to 70°C, stirred at 100 rpm for 4 h, cooled to room temperature, filtered, the solid was washed with deionized water 4 times, dried at 50°C and a vacuum degree of 0.2 kPa for 10 h, ground until it passed through a 400-mesh sieve, and methanol twice the mass of the rice husk powder, ethyl orthosilicate three times the mass of the rice husk powder, and 0.8 mol / L dilute hydrochloric acid once the mass of the rice husk powder were added, stirred at 250 rpm for 30 h, filtered, the solid was washed with deionized water twice, dried at -45°C for 20 h, and calcined at 700°C for 4 h to obtain rice husk carbon composite silica nanospheres;
[0033] (2) Mix the rice husk charcoal composite silica nanospheres with 2-aminoethylaminomethyltriethoxysilane in a mass ratio of 1:1, place in toluene with a mass 25 times that of 2-aminoethylaminomethyltriethoxysilane, heat to 95°C under nitrogen protection, stir at 70 rpm for 10 h, filter, take the solid, wash it twice with dichloromethane and ethanol respectively, and dry it at 80°C and a vacuum degree of 0.2 kPa for 3 h to obtain modified rice husk charcoal composite silica nanospheres;
[0034] (3) The epoxy resin E51 was mixed with hexahydrophthalic anhydride, stirred at 70 rpm for 10 min, ultrasonicated at 20 kHz for 60 min, n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres were added, stirred at 100 rpm for 3 h, extruded and spun at a temperature of 190 ° C, a melt viscosity of 200 Pa × s, and a tensile strength of 8.8 MPa, and cured at 90 ° C for 3 h to obtain epoxy resin fibers; the mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres was 50:46.5:2.3:5;
[0035] (4) 2,4-dihydroxybenzophenone and anhydrous ethanol were mixed in a mass ratio of 20:95 and placed in an ice water bath at 0°C, and an 8 wt% sodium hydroxide aqueous solution of 5.4 times the mass of 2,4-dihydroxybenzophenone was added dropwise at 0.3 mL / s, and the mixture was reacted for 30 min. Dimethyl sulfate of 1.5 times the mass of 2,4-dihydroxybenzophenone was added, and the mixture was stirred at 70 rpm for 10 h. The mixture was filtered, and the solid was taken and washed twice with an 8 wt% sodium hydroxide aqueous solution and anhydrous ethanol, respectively, to obtain intermediate A;
[0036] (5) Intermediate A and N,N-dimethylformamide were mixed in a mass ratio of 9:4, and stirred at 70 rpm for 20 min to obtain a mixed solution; N,N-dimethylformamide was placed in a 0°C ice-water bath, and a mixed solution of phosphorus oxychloride (0.9 times the mass of N,N-dimethylformamide) and 2.8 times the mass of N,N-dimethylformamide were added dropwise at 0.1 mL / s, the temperature was raised to 70°C, and the reaction was performed for 3 h. After cooling to room temperature, 20 times the mass of N,N-dimethylformamide and 0°C deionized water and 1 times the mass of N,N-dimethylformamide were added with a 10 wt% sodium carbonate aqueous solution, filtered, and the solid was taken. After washing once with deionized water, anhydrous ethanol (4 times the mass of N,N-dimethylformamide) was added, and the mixture was allowed to stand for 1 h. The mixture was filtered and the solid was taken to obtain intermediate B;
[0037] (6) Under nitrogen protection, aluminum chloride, intermediate B, and dichloromethane were mixed in a mass ratio of 1.5:1:13, stirred at 70 rpm for 3 h, 6 times the mass of dichloromethane, 0°C deionized water was added, and the solution was adjusted to pH 5 with hydrochloric acid, filtered, the solid was taken, washed once with saturated sodium chloride solution, 5 wt% sodium hydroxide aqueous solution was added until the solution pH was 8, and then dilute hydrochloric acid was added until the solution pH was 5, allowed to stand for 30 min, filtered, the solid was taken, washed once with deionized water, and dried at 50°C for 3 h to obtain modified 2,4-dihydroxybenzophenone;
[0038] (7) aminopolyethylene glycol acrylate, distilled water, and anhydrous ethanol were mixed in a mass ratio of 0.8:0.8:16, and modified 2,4-dihydroxybenzophenone was added in an amount of 4 times the mass of aminopolyethylene glycol acrylate, and stirred at 70 rpm for 4 h. A 0.5 mol / L calcium chloride aqueous solution was added in an amount of 4 times the mass of aminopolyethylene glycol acrylate, and the mixture was soaked at 33° C. for 3 d. Then, No. 90 base asphalt was added in an amount of 36 times the mass of aminopolyethylene glycol acrylate and hexadecyltrimethylammonium chloride was added in an amount of 5 times the mass of aminopolyethylene glycol acrylate, and the mixture was heated to 130° C. and stirred at 3000 rpm for 20 min to obtain modified asphalt.
[0039] (8) The epoxy resin fiber and the modified asphalt are mixed, heated to 105° C., stirred at 150 rpm for 4 h, allowed to stand for 1 h, and silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water are added, and stirred at 20 Hz and 100 rpm for 30 min to obtain rutting-resistant epoxy resin concrete; the mass ratio of the epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water is 1:120:48:160:134:17:1:0.5:30.
[0040] Example 2
[0041] (1) Rice husk powder, sodium hydroxide and deionized water were mixed in a mass ratio of 1:1:4, stirred evenly, heated to 80°C, stirred at 150 rpm for 5 h, cooled to room temperature, filtered, the solid was washed with deionized water for 6 times, dried at 60°C and a vacuum degree of 0.6 kPa for 12.5 h, ground until it passed through a 600-mesh sieve, and methanol 3 times the mass of rice husk powder, ethyl orthosilicate 4.5 times the mass of rice husk powder, and 0.8 mol / L dilute hydrochloric acid 1.5 times the mass of rice husk powder were added, stirred at 275 rpm for 45 h, filtered, the solid was washed with deionized water for 4 times, dried at -47.5°C for 24 h, and calcined at 750°C for 6 h to obtain rice husk carbon composite silica nanospheres;
[0042] (2) Mix the rice husk charcoal composite silica nanospheres with 2-aminoethylaminomethyltriethoxysilane in a mass ratio of 1:1, place in toluene with a mass 27 times that of 2-aminoethylaminomethyltriethoxysilane, heat to 100°C under nitrogen protection, stir at 85 rpm for 12 h, filter, take the solid, wash it twice with dichloromethane and ethanol respectively, and dry it at 95°C and a vacuum degree of 0.6 kPa for 4.5 h to obtain modified rice husk charcoal composite silica nanospheres;
[0043] (3) The epoxy resin E51 was mixed with hexahydrophthalic anhydride, stirred at 85 rpm for 20 min, ultrasonicated at 30 kHz for 80 min, and n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres were added, stirred at 150 rpm for 4.5 h, extruded and spun at a temperature of 210 ° C, a melt viscosity of 225 Pa × s, and a tensile strength of 10.25 MPa, and cured at 110 ° C for 4.5 h to obtain epoxy resin fibers; the mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres was 60:57.5:3.2:6.5;
[0044] (4) 2,4-dihydroxybenzophenone and anhydrous ethanol were mixed in a mass ratio of 22:103, placed in an ice-water bath at 0-4°C, and an 8 wt% sodium hydroxide aqueous solution (6.3 times the mass of 2,4-dihydroxybenzophenone) was added dropwise at 0.5 mL / s, reacted for 45 min, and dimethyl sulfate (1.75 times the mass of 2,4-dihydroxybenzophenone) was added, stirred at 85 rpm for 12 h, filtered, and the solid was taken and washed 3 times with an 8 wt% sodium hydroxide aqueous solution and anhydrous ethanol respectively to obtain intermediate A;
[0045] (5) Intermediate A and N,N-dimethylformamide were mixed in a mass ratio of 9.5:5, and stirred at 85 rpm for 25 min to obtain a mixed solution; N,N-dimethylformamide was placed in a 2°C ice water bath, and phosphorus oxychloride (1 times the mass of N,N-dimethylformamide) was added dropwise at 0.2 mL / s, and the mixed solution (3.1 times the mass of N,N-dimethylformamide) was added, and the temperature was raised to 75°C, and the reaction was carried out for 4.5 h. After cooling to room temperature, 22.5 times the mass of N,N-dimethylformamide and 2°C deionized water and 1.25 times the mass of N,N-dimethylformamide were added. A 10 wt% sodium carbonate aqueous solution was added, and the solid was filtered and washed twice with deionized water. After that, anhydrous ethanol (5.5 times the mass of N,N-dimethylformamide) was added, and the mixture was allowed to stand for 1.5 h, and filtered to obtain a solid to obtain intermediate B;
[0046] (6) Under nitrogen protection, aluminum chloride, intermediate B, and dichloromethane were mixed in a mass ratio of 2.25:1.3:15, stirred at 85 rpm for 4 h, 7 times the mass of dichloromethane and 2°C deionized water were added, and the solution was adjusted to pH 5 with hydrochloric acid, filtered, the solid was taken, washed twice with saturated sodium chloride solution, 5 wt% sodium hydroxide aqueous solution was added until the solution pH was 9, and then dilute hydrochloric acid was added until the solution pH was 5.5, allowed to stand for 45 min, filtered, the solid was taken, washed twice with deionized water, and dried at 60°C for 4.5 h to obtain modified 2,4-dihydroxybenzophenone;
[0047] (7) aminopolyethylene glycol acrylate, distilled water, and anhydrous ethanol were mixed in a mass ratio of 1:1:20, and modified 2,4-dihydroxybenzophenone was added in an amount of 6 times the mass of aminopolyethylene glycol acrylate, and stirred at 85 rpm for 5 h. A 0.5 mol / L calcium chloride aqueous solution was added in an amount of 5 times the mass of aminopolyethylene glycol acrylate, and the mixture was soaked at 37°C for 3 d. Then, No. 90 base asphalt was added in an amount of 40 times the mass of aminopolyethylene glycol acrylate and hexadecyltrimethylammonium chloride was added in an amount of 7.5 times the mass of aminopolyethylene glycol acrylate, and the mixture was heated to 145°C and stirred at 4000 rpm for 30 min to obtain modified asphalt.
[0048] (8) The epoxy resin fiber and the modified asphalt are mixed, the temperature is raised to 117.5° C., and the mixture is stirred at 200 rpm for 6 h. The mixture is allowed to stand for 1.5 h. Portland cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water are added. The mixture is stirred at 25 Hz and 150 rpm for 40 min to obtain rutting-resistant epoxy resin concrete. The mass ratio of the epoxy resin fiber, the modified asphalt, the Portland cement, the limestone coarse particles, the limestone chips, the fly ash, the triterpenoid saponin air entraining agent, the melamine water reducer, and the deionized water is 1.5:140:52:170:144:19:1.1:0.6:35.
[0049] Example 3
[0050] (1) Rice husk powder, sodium hydroxide and deionized water were mixed in a mass ratio of 1.2:1.2:4.4, stirred evenly, heated to 90°C, stirred at 200 rpm for 6 h, cooled to room temperature, filtered, the solid was washed 8 times with deionized water, dried at 70°C and a vacuum degree of 1 kPa for 15 h, ground until it passed through an 800-mesh sieve, and methanol 4 times the mass of rice husk powder, ethyl orthosilicate 6 times the mass of rice husk powder, and 0.8 mol / L dilute hydrochloric acid 2 times the mass of rice husk powder were added, stirred at 300 rpm for 60 h, filtered, the solid was washed 5 times with deionized water, dried at -50°C for 26 h, and calcined at 800°C for 8 h to obtain rice husk carbon composite silica nanospheres;
[0051] (2) Mix the rice husk charcoal composite silica nanospheres with 2-aminoethylaminomethyltriethoxysilane in a mass ratio of 1:1, place in toluene with a mass 30 times that of 2-aminoethylaminomethyltriethoxysilane, heat to 105°C under nitrogen protection, stir at 100 rpm for 14 h, filter, take the solid, wash it twice with dichloromethane and ethanol respectively, and dry it at 110°C and a vacuum degree of 1 kPa for 6 h to obtain modified rice husk charcoal composite silica nanospheres;
[0052] (3) Mix epoxy resin E51 and hexahydrophthalic anhydride, stir at 100 rpm for 30 min, ultrasonicate at 40 kHz for 100 min, add n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres, stir at 200 rpm for 6 h, extrusion spin at a temperature of 230 ° C, a melt viscosity of 250 Pa × s, and a tensile strength of 11.5 MPa, and cure at 120 ° C for 6 h to obtain epoxy resin fibers; the mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres is 70:68.2:4.2:8;
[0053] (4) 2,4-dihydroxybenzophenone and anhydrous ethanol were mixed in a mass ratio of 24:110, placed in a 4°C ice water bath, and an 8 wt% sodium hydroxide aqueous solution (7.2 times the mass of 2,4-dihydroxybenzophenone) was added dropwise at 0.7 mL / s, reacted for 60 min, and dimethyl sulfate (2 times the mass of 2,4-dihydroxybenzophenone) was added, stirred at 100 rpm for 14 h, filtered, and the solid was taken and washed 4 times with an 8 wt% sodium hydroxide aqueous solution and anhydrous ethanol, respectively, to obtain intermediate A;
[0054] (5) Intermediate A and N,N-dimethylformamide were mixed in a mass ratio of 10:6, and stirred at 100 rpm for 30 min to obtain a mixed solution; N,N-dimethylformamide was placed in a 4°C ice water bath, and a mixed solution of phosphorus oxychloride (1.1 times the mass of N,N-dimethylformamide) and 3.4 times the mass of N,N-dimethylformamide were added dropwise at 0.3 mL / s, the temperature was raised to 80°C, the reaction was performed for 6 h, and after cooling to room temperature, 25 times the mass of N,N-dimethylformamide and 4°C deionized water and 1.5 times the mass of N,N-dimethylformamide were added with a 10 wt% sodium carbonate aqueous solution, filtered, and the solid was taken. After washing with deionized water 3 times, anhydrous ethanol (7 times the mass of N,N-dimethylformamide) was added, and the mixture was allowed to stand for 2 h, filtered, and the solid was taken to obtain intermediate B;
[0055] (6) Under nitrogen protection, aluminum chloride, intermediate B, and dichloromethane were mixed in a mass ratio of 3:1.7:17, stirred at 100 rpm for 6 h, 8 times the mass of dichloromethane and 4°C deionized water were added, and the solution was adjusted to pH 5 with hydrochloric acid, filtered, the solid was taken, washed 3 times with saturated sodium chloride solution, 5 wt% sodium hydroxide aqueous solution was added until the solution pH was 10, and then dilute hydrochloric acid was added until the solution pH was 6, allowed to stand for 60 min, filtered, the solid was taken, washed 3 times with deionized water, and dried at 70°C for 6 h to obtain modified 2,4-dihydroxybenzophenone;
[0056] (7) aminopolyethylene glycol acrylate, distilled water, and anhydrous ethanol were mixed in a mass ratio of 1.2:1.2:24, and modified 2,4-dihydroxybenzophenone was added in an amount of 8 times the mass of aminopolyethylene glycol acrylate, and stirred at 100 rpm for 6 h. A 0.5 mol / L calcium chloride aqueous solution was added in an amount of 6 times the mass of aminopolyethylene glycol acrylate, and the mixture was soaked at 40°C for 3 d. Then, No. 90 base asphalt was added in an amount of 44 times the mass of aminopolyethylene glycol acrylate and hexadecyltrimethylammonium chloride was added in an amount of 10 times the mass of aminopolyethylene glycol acrylate, and the mixture was heated to 160°C and stirred at 5000 rpm for 40 min to obtain modified asphalt.
[0057] (8) The epoxy resin fiber and the modified asphalt are mixed, the temperature is raised to 130° C., and the mixture is stirred at 250 rpm for 8 h. The mixture is allowed to stand for 2 h. Portland cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water are added. The mixture is stirred at 30 Hz and 200 rpm for 50 min to obtain rutting-resistant epoxy resin concrete. The mass ratio of the epoxy resin fiber, modified asphalt, Portland cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water is 2:160:56:180:154:21:1.2:0.7:40.
[0058] Comparative Example 1
[0059] The difference between Comparative Example 1 and Example 2 is that step (1) and step (2) are omitted, and step (3) is changed to: epoxy resin E51 and hexahydrophthalic anhydride are mixed, stirred at 85 rpm for 20 min, ultrasonicated at 30 kHz for 80 min, extruded and spun at a temperature of 210° C., a melt viscosity of 225 Pa×s, and a tensile strength of 10.25 MPa, and cured at 110° C. for 4.5 h to obtain epoxy resin fiber; the mass ratio of the epoxy resin E51 to the hexahydrophthalic anhydride is 60:57.5; and the remaining steps are the same as those in Example 2.
[0060] Comparative Example 2
[0061] The difference between Comparative Example 2 and Example 2 is that there is no step (1), and step (2) is changed to: silica nanospheres and 2-aminoethylaminomethyltriethoxysilane are mixed in a mass ratio of 1:1, placed in toluene with a mass of 27 times that of 2-aminoethylaminomethyltriethoxysilane, heated to 100° C. under nitrogen protection, stirred at 85 rpm for 12 h, filtered, and the solid was taken, washed twice with dichloromethane and ethanol respectively, and dried at 95° C. and a vacuum degree of 0.6 kPa for 4.5 h to obtain modified silica nanospheres; step (3) is changed to: epoxy resin E51 and hexahydrophthalic anhydride The mixture was mixed, stirred at 85 rpm for 20 min, and ultrasonicated at 30 kHz for 80 min. n-butyl glycidyl ether and modified silica nanospheres were added, and stirred at 150 rpm for 4.5 h. Extrusion spinning was performed at a temperature of 210° C., a melt viscosity of 225 Pa×s, and a tensile strength of 10.25 MPa. The mixture was cured at 110° C. for 4.5 h to obtain epoxy resin fibers. The mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres was 60:57.5:3.2:6.5. The remaining steps were the same as those in Example 2.
[0062] Comparative Example 3
[0063] The difference between Comparative Example 3 and Example 2 is that step (3) is different. Step (3) is changed to: epoxy resin E51, n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres are mixed, stirred at 150 rpm for 4.5 hours, extruded and spun at a temperature of 210°C, a melt viscosity of 225 Pa×s, and a tensile strength of 10.25 MPa, and cured at 110°C for 4.5 hours to obtain epoxy resin fibers; the mass ratio of the epoxy resin E51, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres is 60:3.2:6.5; the remaining steps are the same as Example 2.
[0064] Comparative Example 4
[0065] The difference between Comparative Example 4 and Example 2 is that step (1), step (2) and step (3) are omitted, and step (8) is changed to: modified asphalt, silicate cement, limestone coarse particles, limestone debris, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water are stirred at 25 Hz and 150 rpm for 40 min to obtain rutting-resistant epoxy resin concrete; the mass ratio of the modified asphalt, silicate cement, limestone coarse particles, limestone debris, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water is 140:52:170:144:19:1.1:0.6:35; and the remaining steps are the same as in Example 2.
[0066] Comparative Example 5
[0067] The difference between Comparative Example 5 and Example 2 is that step (4), step (5), step (6) and step (7) are omitted; step (8) is changed to: epoxy resin fiber, silicate cement, limestone coarse particles, limestone debris, fly ash, triterpenoid saponin air entraining agent, melamine water reducer and deionized water are stirred at 25 Hz and 150 rpm for 40 min to obtain rutting-resistant epoxy resin concrete; the mass ratio of the epoxy resin fiber, silicate cement, limestone coarse particles, limestone debris, fly ash, triterpenoid saponin air entraining agent, melamine water reducer and deionized water is 1.5:52:170:144:19:1.1:0.6:35; the remaining steps are the same as in Example 2.
[0068] Comparative Example 6
[0069] The difference between Comparative Example 6 and Example 2 is that steps (4), (5) and step (6) are omitted, and step (7) is changed to: 2,4-dihydroxybenzophenone and a 0.5 mol / L calcium chloride aqueous solution with a mass of 5 times that of 2,4-dihydroxybenzophenone are soaked at 37° C. for 3 days, and then No. 90 base asphalt with a mass of 40 times that of 2,4-dihydroxybenzophenone and hexadecyltrimethylammonium chloride with a mass of 7.5 times that of 2,4-dihydroxybenzophenone are added, the temperature is raised to 145° C., and stirred at 4000 rpm for 30 min to obtain modified asphalt; the remaining steps are the same as those in Example 2.
[0070] Comparative Example 7
[0071] The difference between Comparative Example 7 and Example 2 is that step (7) is different. Step (7) is changed to: aminopolyethylene glycol acrylate, distilled water and anhydrous ethanol are mixed in a mass ratio of 1:1:20, modified 2,4-dihydroxybenzophenone is added in an amount of 6 times the mass of aminopolyethylene glycol acrylate, and stirred at 85 rpm for 5 h, No. 90 base asphalt is added in an amount of 40 times the mass of aminopolyethylene glycol acrylate and hexadecyltrimethylammonium chloride is added in an amount of 7.5 times the mass of aminopolyethylene glycol acrylate, the temperature is raised to 145°C, and stirred at 4000 rpm for 30 min to obtain modified asphalt; the remaining steps are the same as those in Example 2.
[0072] Effect example
[0073] Table 1 below shows the performance analysis results of the rutting-resistant epoxy resin concrete using Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.
[0074] Table 1
[0075]
[0076] From the comparison of the compressive strength test data of the embodiment and the comparative example in Table 1, it can be found that the present invention uses 2-aminoethylaminomethyltriethoxysilane to modify the rice husk carbon silicon composite silica nanospheres, and after melt spinning with epoxy resin and hexahydrophthalic anhydride, heat treatment is performed to form covalent bonds, which can absorb a large amount of energy and generate holes when subjected to external force, so that the local strain capacity of the epoxy resin cross-linking network is improved, the expansion of silver streaks in the matrix is effectively suppressed, and the role of strengthening the epoxy resin is played, thereby achieving the effect of compressive resistance; at the same time, with the assistance of the nanospheres, the epoxy resin fibers are interspersed in the interior of the concrete to form A stable three-dimensional cross-linked structure is formed to support the structure and enhance the compressive resistance of the concrete. From the comparison of the carbonization depth data of the embodiment and the comparative example in Table 1, it can be found that the aldehyde group introduced by 2,4-dihydroxybenzophenone reacts with aminopolyethylene glycol acrylate to form a conjugated system in the asphalt, which shields and absorbs ultraviolet rays and achieves a strong anti-ultraviolet effect. Then, the hydroxyl group is combined with calcium ions to form a dense and locked structure inside the concrete, which jointly bears external forces and enhances compressive resistance. At the same time, the compatibility of aminopolyethylene glycol acrylate and asphalt is also enhanced, thereby enhancing the anti-ultraviolet effect of the concrete.
[0077] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. An anti-rutting epoxy resin concrete, characterized in that: The anti-rutting epoxy resin concrete is prepared from epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone debris, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water; the preparation method of the anti-rutting epoxy resin concrete comprises the following preparation steps: (1) Rice husk powder, sodium hydroxide and deionized water were mixed in a mass ratio of 0.8:0.8:3.6~1.2:1.2:4.4, stirred evenly, heated to 70~90°C, stirred at 100~200rpm for 4~6h, cooled to room temperature, filtered, solid was washed with deionized water for 4~8 times, vacuum dried at 50~70°C for 10~15h, ground until it passed through a 400~800 mesh sieve, added with methanol 2~4 times the mass of rice husk powder, ethyl orthosilicate 3~6 times the mass of rice husk powder, and 0.8 mol / L dilute hydrochloric acid 1~2 times the mass of rice husk powder, stirred at 250~300rpm for 30~60h, filtered, solid was washed with deionized water 2~5 times, dried at -45~-50°C for 20~26h, and calcined at 700~800°C for 4~8h to obtain rice husk carbon composite silica nanospheres; (2) Mix the rice husk charcoal composite silica nanospheres with 2-aminoethylaminomethyltriethoxysilane in a mass ratio of 1:1, place in toluene with a mass of 25 to 30 times that of 2-aminoethylaminomethyltriethoxysilane, heat to 95 to 105°C under nitrogen protection, stir at 70 to 100 rpm for 10 to 14 h, filter, take the solid, wash it twice with dichloromethane and ethanol respectively, and vacuum dry it at 80 to 110°C for 3 to 6 h to obtain modified rice husk charcoal composite silica nanospheres; (3) Epoxy resin E51 was mixed with hexahydrophthalic anhydride, stirred at 70-100 rpm for 10-30 min, ultrasonicated at 20-40 kHz for 60-100 min, n-butyl glycidyl ether and modified rice husk charcoal composite silica nanospheres were added, stirred at 100-200 rpm for 3-6 h, melt-spun at 190-230 °C, melt viscosity of 200-250 Pa×s, and tensile strength of 8.8-11.5 MPa, and cured at 90-120 °C for 3-6 h to obtain epoxy resin fibers; (4) Mix 2,4-dihydroxybenzophenone and anhydrous ethanol in a mass ratio of 20:95-24:110 and place in an ice water bath at 0-4°C, add 8wt% sodium hydroxide aqueous solution (5.4-7.2 times the mass of 2,4-dihydroxybenzophenone) dropwise at 0.3-0.7 mL / s, react for 30-60 min, add dimethyl sulfate (1.5-2 times the mass of 2,4-dihydroxybenzophenone), stir at 70-100 rpm for 10-14 h, filter, take the solid, wash with 8wt% sodium hydroxide aqueous solution and anhydrous ethanol 2-4 times each, to obtain intermediate A; (5) Mix intermediate A and N,N-dimethylformamide in a mass ratio of 9:4-10:6, and stir at 70-100 rpm for 20-30 min to obtain a mixed solution; place N,N-dimethylformamide in an ice water bath at 0-4°C, and add a mixed solution of phosphorus oxychloride (0.9-1.1 times the mass of N,N-dimethylformamide) and 2.8-3.4 times the mass of N,N-dimethylformamide at a rate of 0.1-0.3 mL / s; Heat to 70-80°C, react for 3-6 hours, cool to room temperature, add 0-4°C deionized water (20-25 times the mass of N,N-dimethylformamide) and 1-1.5 times the mass of N,N-dimethylformamide 10wt% sodium carbonate aqueous solution, filter, take the solid, wash with deionized water 1-3 times, add anhydrous ethanol (4-7 times the mass of N,N-dimethylformamide), let stand for 1-2 hours, filter, take the solid, and obtain intermediate B; (6) Under nitrogen protection, aluminum chloride, intermediate B, and dichloromethane were mixed in a mass ratio of 1.5:1:13~3:1.7:17, stirred at 70~100 rpm for 3~6 hours, 6~8 times the mass of dichloromethane, 0~4°C deionized water was added, and the solution was adjusted to pH 5 with hydrochloric acid, filtered, the solid was taken, washed with saturated sodium chloride solution 1~3 times, 5wt% sodium hydroxide aqueous solution was added to the solution pH of 8~10, and then dilute hydrochloric acid was added to the solution pH of 5~6, and allowed to stand for 30~60 minutes, filtered, the solid was taken, washed with deionized water 1~3 times, and dried at 50~70°C for 3~6 hours to obtain modified 2,4-dihydroxybenzophenone; (7) Mix amino polyethylene glycol acrylate, distilled water and anhydrous ethanol in a mass ratio of 0.8:0.8:16-1.2:1.2:24, add modified 2,4-dihydroxybenzophenone in an amount of 4-8 times the mass of amino polyethylene glycol acrylate, stir at 70-100 rpm for 4-6 hours, add 0.5 mol / L calcium chloride aqueous solution in an amount of 4-6 times the mass of amino polyethylene glycol acrylate, soak at 33-40°C for 3 days, then add No. 90 base asphalt in an amount of 36-44 times the mass of amino polyethylene glycol acrylate and hexadecyltrimethylammonium chloride in an amount of 5-10 times the mass of amino polyethylene glycol acrylate, heat to 130-160°C, stir at 3000-5000 rpm for 20-40 minutes to obtain modified asphalt; (8) Mix the epoxy resin fiber with the modified asphalt, heat it to 105-130°C, stir it at 150-250 rpm for 4-8 h, let it stand for 1-2 h, add silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer, and deionized water, and stir it at 20-30 Hz and 100-200 rpm for 30-50 min to obtain rutting-resistant epoxy resin concrete.
2. The anti-rutting epoxy resin concrete according to claim 1, characterized in that: The vacuum in step (1) and step (2) is 0.2-1 kPa.
3. The anti-rutting epoxy resin concrete according to claim 1, characterized in that: In step (3), the mass ratio of the epoxy resin E51, hexahydrophthalic anhydride, n-butyl glycidyl ether, and modified rice husk charcoal composite silica nanospheres is 50:46.5:2.3:5-70:68.2:4.2:
8.
4. The anti-rutting epoxy resin concrete according to claim 1, characterized in that: In step (8), the mass ratio of the epoxy resin fiber, modified asphalt, silicate cement, limestone coarse particles, limestone chips, fly ash, triterpenoid saponin air entraining agent, melamine water reducer and deionized water is 1:120:48:160:134:17:1:0.5:30~2:160:56:180:154:21:1.2:0.7:40.
Citation Information
Patent Citations
Anti-aging asphalt for muck truck road and preparation method of anti-aging asphalt
CN114854222A
Anti-rutting and anti-aging concrete and preparation method thereof
CN115403330A
